Compensation for Losses of Land Ownership Rights for Public Interest in the Betoambari Baubau Airport Area - Raydattul Jannah, Ghira; Isnaeni, Diyan; Sunardi, Sunardi (Journal of Law, Politic and Humanities, 2025)
Development for public interest requires land as one of the important aspects that supports the success of its implementation. However, the problem is that the land controlled by the state is limited. Based on this situation, the government carries out land acquisition by using individual or legal entity land that has been controlled for the public interest. In this case, Betoambari Airport in Baubau City is carrying out development, namely expanding the runway area which requires land around the airport area. This study uses an empirical legal research method with a conceptual approach and a legal approach, both of which are interconnected from concepts and laws and regulations. The results of the study in the implementation of compensation for land rights together with the release of land for the expansion of the Betoambari Airport area in Baubau City have been carried out in 2 stages totaling 23 plots of land with a total area of 34,177 M². The obstacles that occur are that there are land certificates of owners that have been mortgaged to obtain loans at the bank. In an effort to overcome these obstacles, the city government provides time to complete the installments of the bank loan and encourages the community involved in the loan to complete the obligations of the certificate owner